Comparison of Some Methods for Estimating Poisson Regression Model Parameters Using the Genetic Algorithm - Redha, Sabah Manfi; Saleh, Rabab Abdulrida; Abdullatif, Adila (International Journal of Psychosocial Rehabilitation, 2020)
The Poisson regression model is one of the log- linear most important models and this model is suitable for analyzing data in the form of a Counting data Or rates This model deals with the effects of the response variable that are rare in This paper, the procedure for the maximum likelihood estimation of the regression coefficient apply for Poisson regression and the Bayesian Poisson regression using some of Artificial intelligence algorithms